2007
DOI: 10.1086/520978
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Drug Interaction between Itraconazole and Efavirenz in a Patient with AIDS and Disseminated Histoplasmosis

Abstract: Although there is a presumed drug-drug interaction between itraconazole and nonnucleoside reverse-transcriptase inhibitors, the medical literature lacks such documentation. We describe a drug-drug interaction between itraconazole and efavirenz in a patient with disseminated histoplasmosis and acquired immunodeficiency syndrome (AIDS). The drug combination resulted in persistently elevated urinary Histoplasma antigen levels and subtherapeutic plasma itraconazole concentrations. Changing treatment from efavirenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…10 The first case described an HIV-infected patient diagnosed with histoplasmosis who was receiving an efavirenz-based antiretroviral regimen. 9 The patient was initiated on itraconazole capsules at 200 mg daily for several months, but the urine Histoplasma antigen did not decrease below 4.28 U. A 12-hour plasma itraconazole concentration measured after more than 1 year of itraconazole therapy revealed undetectable levels.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…10 The first case described an HIV-infected patient diagnosed with histoplasmosis who was receiving an efavirenz-based antiretroviral regimen. 9 The patient was initiated on itraconazole capsules at 200 mg daily for several months, but the urine Histoplasma antigen did not decrease below 4.28 U. A 12-hour plasma itraconazole concentration measured after more than 1 year of itraconazole therapy revealed undetectable levels.…”
Section: Discussionmentioning
confidence: 94%
“…5 In addition, this study did not include measurement of PI and NNRTI concentrations to determine the effects of itraconazole on antiretroviral therapy. 11 Because of the potential for low itraconazole concentrations reported with efavirenz, 9 we decided to substitute lopinavir/ritonavir for efavirenz in our patient. Lopinavir trough concentrations before and after initiation of itraconazole were essentially unchanged and were well above the suggested minimum trough concentrations of 1 mg/L recommended for antiretroviral-naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…The infection occurs more often in patients with a CD4 count <50 cells/mm 3 and is usually disseminated (Carme et al 1990). An extremely interesting study showed that the treatment of a patient with AIDS and disseminated histoplasmosis with a combined therapy of itraconazole and HIV peptidase inhibitors (atazanavir, 300 mg once daily, and ritonavir, 100 mg once daily) promoted an improvement in the desired urinary Histoplasma antigen level and plasma itraconazole concentration, leading to a mycological cure (Koo et al 2007). …”
Section: Histoplasma Capsulatummentioning
confidence: 99%
“…May increase plasma concentrations of PIs (such as indinavir, ritonavir and saquinavir) Caution [9] Nevirapine reduced exposure to itraconazole: Cmax 38%, AUC 61%, t 31% [74] Coadministration not recommended [9] Efavirenz reduced exposure to itraconazole in an AIDS patient [75] Voriconazole Voriconazole increased exposure to efavirenz: Cmax 37%, AUC 43%…”
Section: Pis Nrtis Nnrtismentioning
confidence: 99%
“…NNRTIs are CYP3A4 substrates, inhibitors, or CYP450 inducers; and PIs are CYP3A4 substrates and inhibitors. Table 3 summarizes the azoles' interactions with these drug classes [3,9,37,[72][73][74][75][76][77][78][79].…”
Section: Patients With Hiv Infectionmentioning
confidence: 99%